1999
DOI: 10.1103/physrevlett.83.2054
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Roughening of Penetrating Flux Fronts in High-TcThin Film Superconductors

Abstract: Kinetic roughening of flux fronts penetrating in superconducting thin films are studied by means of a high resolution magneto-optic technique. The roughening exponent ͑a 0.64͒ and growth exponent ͑b 0.65͒ obtained from a dynamic scaling analysis of the initial stage of flux penetration and, at small length scales, are characteristic for a static disorder dominated nonlinear diffusion such as also observed in the directed percolated depinning model. At large length scale, a 0.46 indicates a transition towards d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 17 publications
6
66
1
Order By: Relevance
“…In an earlier experiment [14] x 0.71͑5͒ was found and interpreted in terms of the moving phase of the DPD model. Very recently, a crossover to TKPZ scaling was also seen in kinetic roughening of penetrating flux fronts in high-T c thin film superconductors [15]. The SR scaling was purported to be the same as that reported in Ref.…”
Section: Scaling and Noise In Slow Combustion Of Papersupporting
confidence: 64%
“…In an earlier experiment [14] x 0.71͑5͒ was found and interpreted in terms of the moving phase of the DPD model. Very recently, a crossover to TKPZ scaling was also seen in kinetic roughening of penetrating flux fronts in high-T c thin film superconductors [15]. The SR scaling was purported to be the same as that reported in Ref.…”
Section: Scaling and Noise In Slow Combustion Of Papersupporting
confidence: 64%
“…While the Bean model provides a consistent picture of average magnetization properties, such as the hysteresis loop and thermal relaxation effects [30], it does not account for local fluctuations in time and space. It has been recently observed that flux line dynamics is intermittent, taking place in avalanches [31], and flux fronts are not smooth [32][33][34]. In particular, it has been shown that the flux front crosses over from flat to fractal as a function of material parameters and applied field [33].…”
Section: Gradient Driven Dynamics: Front Invasionmentioning
confidence: 99%
“…This is clearly illustrated nowadays by the large variety of studies dealing with front invasion where roughening processes take place such as flow through porous media [16][17][18] or imbibition [19], flame propagation [20,21], deposition processes [14,15], and flux penetration in superconducting materials [32,33,45,46]. From a macroscopic point of view, the development of modeling techniques for the description of these dynamical systems has been generally based on the traditional approach to transport phenomena, where the governing expressions are usually differential equations representing local balances of the quantity of interest (e.g., mass, momentum, flux of superconducting vortices, etc.)…”
Section: Gradient Driven Dynamics: Front Invasionmentioning
confidence: 99%
“…Recent experiments on slow-combustion fronts propagating in paper [4,5], and on flux fronts penetrating a high-T c thin-film superconductor [6], have provided new insight into this problem [7]. It indeed appears that short-range-correlated noise, quenched and dynamical, with possibly at the same time a non-Gaussian amplitude distribution for small time differences, induce an additional time and an additional length scale, beyond which KPZ scaling can only be observed.…”
Section: Introductionmentioning
confidence: 99%